2005
DOI: 10.1038/sj.ejcn.1602149
|View full text |Cite
|
Sign up to set email alerts
|

Iron intake and dietary sources of iron in Flemish adolescents

Abstract: Objective: To investigate the dietary iron intake and food sources of iron in Flemish adolescents. Design: Cross-sectional survey; dietary assessment method: a 7-day estimated food record. Setting: Private and public secondary schools in Ghent, a city in the Dutch-speaking part of Belgium. Subjects: A total of 341 adolescents (129 boys and 212 girls), 13-18 y, randomly selected by a multistage clustered sampling technique. Results: The mean total iron intake (s.d.) for boys was 13.4 (72.91) mg/day and for girl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
(26 reference statements)
1
10
0
Order By: Relevance
“…The qualitative analysis of iron intake showed that a significant number of models had mean intakes below the EAR. Studies conducted both here in Brazil and internationally have shown inadequate iron intake among adolescents (3,29) . An earlier study of 110 models showed a 15.5% prevalence of anemia, which is a worrying figure when one is dealing with models whose daily routine is one of tests and shows that often take the entire day and may contribute to inadequate nutrition because of missing meals that are important for iron intake (such as a midday meal).…”
Section: Discussionmentioning
confidence: 66%
“…The qualitative analysis of iron intake showed that a significant number of models had mean intakes below the EAR. Studies conducted both here in Brazil and internationally have shown inadequate iron intake among adolescents (3,29) . An earlier study of 110 models showed a 15.5% prevalence of anemia, which is a worrying figure when one is dealing with models whose daily routine is one of tests and shows that often take the entire day and may contribute to inadequate nutrition because of missing meals that are important for iron intake (such as a midday meal).…”
Section: Discussionmentioning
confidence: 66%
“…Long term, inadequate iron intake can lead to iron deficiency anaemia, loss of appetite, lassitude, delayed psychomotor and cognitive infant and child development and lower resistance to infection. 2,3 Pynaert et al 4 reported insufficient iron intakes among Belgian adolescents investigated in 1997, with 99.5% of the 13 --18-yearold girls and 38.8% of the boys not reaching Belgian dietary recommendations. 4 When bioavailable iron was considered (using absorption factors of 25% for haem iron 3 and 10% for non-haem iron, 5 84.5% of the adolescent boys and only 16.5% of the girls met the age-specific requirement.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Pynaert et al 4 reported insufficient iron intakes among Belgian adolescents investigated in 1997, with 99.5% of the 13 --18-yearold girls and 38.8% of the boys not reaching Belgian dietary recommendations. 4 When bioavailable iron was considered (using absorption factors of 25% for haem iron 3 and 10% for non-haem iron, 5 84.5% of the adolescent boys and only 16.5% of the girls met the age-specific requirement. 4 However, there are no data related to the intake of bioavailable iron among Belgian children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale for this research was the low iron intake found in Flemish adolescent girls (Pynaert et al, 2005). The study in adult women was aimed at exploring to what extent this low iron intake persists later in life and whether a low iron intake is also reflected in a low iron status.…”
Section: Introductionmentioning
confidence: 99%